Towarzyskie zawody piłkarskie Zawisza Bydgoszcz-Lechia Gdańsk. (Gdynia : [s.n.], 1966)
Afisz inf. o meczu 13.03.1966.
Keywords: Lechia Gdańsk -- 1945-1970 -- druki ulotne; Piłka nożna -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne